2017
DOI: 10.1089/lgbt.2016.0117
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation-Based Discrimination, Excessive Alcohol Use, and Substance Use Disorders Among Sexual Minority Adults

Abstract: Sexual orientation-based discrimination was associated with select substance use outcomes, especially among bisexuals, Hispanics, and less educated sexual minority adults, highlighting potential disparities associated with experiencing discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
84
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 33 publications
11
84
1
2
Order By: Relevance
“…In this national US study of reported discrimination among LGBTQ adults, four key findings emerge. First, study results extend prior findings that LGBTQ adults in the United States experience pervasive discrimination across many areas of life . In particular, we found widespread interpersonal manifestations, including slurs, harassment, and violence.…”
Section: Discussionsupporting
confidence: 84%
“…In this national US study of reported discrimination among LGBTQ adults, four key findings emerge. First, study results extend prior findings that LGBTQ adults in the United States experience pervasive discrimination across many areas of life . In particular, we found widespread interpersonal manifestations, including slurs, harassment, and violence.…”
Section: Discussionsupporting
confidence: 84%
“…This chronic minority stress arises from a range of experiences, such as discrimination, victimization, and interpersonal rejection based on one’s sexual orientation (Meyer, 2003). Minority stress has been identified as a major mechanism underlying the substantial sexual orientation-related disparities observed in mental health (Bränström, Hatzenbuehler, & Pachankis, 2016; Eaton, 2014; Hatzenbuehler, McLaughlin, Keyes, & Hasin, 2010) and substance use (Lehavot & Simoni, 2011; McCabe, Bostwick, Hughes, West, & Boyd, 2010; Slater, Godette, Huang, Ruan, & Kerridge, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…SM‐related discrimination has been found to be associated with increased tobacco, alcohol and drug use in SM populations , although differentially associated with substance use across SM identities . We found that while SM‐related discrimination was significantly higher among SM, discrimination was not significantly associated with SUD among SM‐identifying individuals.…”
Section: Discussionmentioning
confidence: 49%
“…Effective strategies to incorporate social support may require assessing the functional support received and tailoring interventions based on social networks. SM-related discrimination has been found to be associated with increased tobacco, alcohol and drug use in SM populations [13,17,62,63], although differentially associated with substance use across SM identities [8,13,64]. We found that while SM-related discrimination was significantly higher among SM, discrimination was not significantly associated with SUD among SM-identifying individuals.…”
Section: Discussionmentioning
confidence: 50%